Growing Out of the Tropical Forests: Gene Flow of Native Mesoamerican Trees Among Forest and Mayan Homegardens - Ferrer, Miriam M.; Tapia-Gómez, Cristell A.; Estrada-Medina, Héctor; Ruenes-Morales, María del Rocío; Montañez-Escalante, Patricia I.; Jiménez-Osornio, Juan J. (Frontiers in Ecology and Evolution, 2021)
This work aimed to evaluate domestication effects on the genetic structure of two dioecious species Brosimum alicastrum Sw. (Moraceae) and Spondias purpurea L. (Anacardiaceae), and a heterostylous one Cordia dodecandra A. DC. (Cordiaceae), growing in remnant forests and homegardens within two climatic regions of the Peninsula of Yucatan. The trees of B. alicastrum and C. dodecandra are propagated by seeds in both population types, while those of S. purpurea are propagated asexually in the homegardens. ISSRs genetic markers were amplified from foliar tissue of 18 to 21 plants per population type/region combination for each species. Genetic diversity, genetic differentiation, and genetic structure estimators were obtained and compared among species at the regional and population level. We found higher polymorphism (37.5-41), but lower private alleles (4-4.4) and similar heterozygosity (0.1-0.12) in the species with sexual reproduction compared to S. purpurea (34, 8, and 0.11, respectively). Genetic diversity in B. alicastrum populations varied with the region; in C. dodecandra, to the population type; and in S. purpurea, to both the population type and the region. Unrestricted gene flow among regions was suggested by low RT in C. dodecandra and S. purpurea (-0.006 and 0.002) but not for B. alicastrum (0.1). Gene flow between populations within the regions for the sexually reproducing species was suggested by lower II (0.005-0.07 and 0.008-0.1) estimates than those of S. purpurea (0.09 and 0.13). Even though the lowest paired FST (0.002-0.05) and ST (0.002-0.12) values were found between the northeastern forest and homegarden populations for the three species, the dendrogram, Bayesian assignment, and K-Means analyses suggest that the least differentiated populations are southwestern forest and homegarden populations of B. alicastrum and S. purpurea, and the southwestern forest and northeastern homegarden of C. dodecandra. The sexual reproduction, biotic interactions, and extensive management of B. alicastrum and C. dodecandra in the agroforestry and the urban systems may contribute to connectivity between wild and domesticated populations, while in S. purpurea this connectivity is interrupted by the clonal propagation of the species in the homegardens.